Hope as a predictor for COVID-19 vaccine uptake. Issue 12 (2nd December 2021) - Mayer, Yael; Etgar, Shir; Shiffman, Noga; Bloch, Yuval; Mendlovic, Shlomo; Lurie, Ido
ABSTRACT: The worldwide effort to recover from the COVID-19 crisis is now at its pinnacle with the putative vaccine against SARS-CoV-2. To reach herd immunity, it has become an urgent global need to understand the emotional factors that drive people's choice to get vaccinated. Therefore, this exploratory study examined emotional motivations as predictors of the decision to receive the vaccine. The sample ( N = 627) included adult (18+) participants in Israel who were recruited by a snowball sampling. The participants filled out an online survey when the vaccines have become widely available in Israel. Within the entire sample, as well as among people who did not receive the vaccine yet, hope was the only factor that was associated with their willingness to be vaccinated; higher levels of hope were related to willingness to be vaccinated. The results of the study indicate that hope is an important factor related to motivation to receive the SARS-CoV-2 vaccine.